Predictive Models of Business Value Management - Kaganovskyi Oleksandr S.; Chmutova Iryna M. (Problemi Ekonomiki)
The aim of the article is to build a model of value management, evaluation and analysis of the process of simulation of the value of enterprise, based on different approaches and methods, taking into account important factors and aspects that are directly related to the identification of the most significant advantages and disadvantages. Olson and Evans models were used to determine the value of the enterprise. Olson’s model has significant advantages: when calculating value, this model minimizes the disadvantages of the profit approach and defines the value of an enterprise as the current value of its net assets and discounted income flow. In the Evans model and the discounted money flow model, there are a number of advantages over other valuation methods. In accordance with the selected assessment methods, the set and amount of necessary information is determined. Information can be drawn from several sources, such as: the evaluated company, the stock market, various statistical information, marketing research, etc. Business valuation requires standardized data reflecting the real market and economic position of the company. The article uses the available statistical reporting of enterprise, which allowed to determine the value of enterprise and its limit of variation. The authors implemented the necessary calculation procedures provided for by the selected methods of business valuation: building the selected models for assessing the value of the business (Olson, Evans, discounted money flow model) and conducting experiments on changes in the coefficients used in the models. The calculation of the value of enterprise using the Olson model on the basis of the Evans model and discounted money flow is carried out. Several experiments have been conducted to determine the size of the enterprise value, depending on the coefficients used in the models. Analysis of the results obtained allows us to say that the enterprise with its further development will not cease to exist and will develop at a fairly rapid pace.